Effect of HiHiLo on autonomic nervous system and body functional status of excellent female rowers - Gao, B.; Zhang, Y.; Gao, H. (Exercise Biochemistry Review, 2018)
Objective 12 female rowing athletes of Shanghai as research object of this study. 7 weeks of hypoxic experiment will be carried out on the study subjects. Monitoring of HRV and functional indexes of athletes during this period. To explore the effect of 3 weeks of Living High Training High Training Low(HiHiLo) training of female rowers ANS and functional status, and discussion on the relationship between ANS and functional status of athletes in HiHiLo.